Comparison of socio-economic and ecological benefits of bamboo and trees: the perspectives of local communities in south-western Ghana. Issue 3 (3rd July 2019) - Osei, Richard; Ansong, Michael; Zerbe, Stefan
Abstract : Natural forests are disappearing in many tropical countries, resulting in loss of biodiversity and erosion of forest-dependent livelihoods. The maintenance and restoration of forests as well as a search for alternative natural resources that can concurrently improve the environment and enhance incomes of local communities has become crucial. Bamboo is suggested as a resource, which could substitute trees for socio-economic and ecological purposes in developing countries in the (sub)tropics. However, the relative importance of bamboos and trees for socio-economic and ecological purposes in bamboo-growing communities is not yet studied. Here, we present a study conducted to compare the socio-economic and ecological benefits of bamboo and trees from the perspectives of three bamboo-growing communities in the Wassa East District of Ghana. The compared benefits were ranked on a five-point Likert scale and significance of differences was tested at the 95% confidence level. For socio-economic benefits, trees were ranked significantly higher than bamboo for domestic energy, medicinal use and commercial harvesting; however, furniture, building and construction were not significantly different. For ecological benefits, bamboo was ranked significantly higher than trees for erosion control and riverbank protection. Trees, on the other hand, were ranked significantly higher than bamboo for biodiversity conservation, carbon sequestration and oxygen generation. The results imply that transforming bamboo into suitable products to meet communities' energy needs could alleviate pressure on trees in natural forests.